Qāʿidah Darʾ al-Mafāsid Muqaddam ʿalā Jalb al-Maṣāliḥ wa-Taṭbīquhā fī Qaḍāyā al-Aḥwāl al-Shakhṣiyyah - Fadilla; Yuli Yasin; Aeshah Ahmed Salim Hasan (Al-Zahra : Journal for Islamic and Arabic Studies, 2025)
This study examines the application of the jurisprudential maxim “darʾ al-mafāsid muqaddam ʿalā jalb al-maṣāliḥ” (Averting harm takes precedence over procuring benefit) in the domain of personal status law, with particular reference to early marriage, polygamy without spousal consent, and marital dissolution on the grounds of infertility. These issues simultaneously encompass both potential benefits and harms. The objective of this research is to elucidate the manner in which legal maxims function as analytical tools for engaging with contemporary legal challenges, particularly within the framework of Islamic family law. Methodologically, this research adopts a descriptive-analytical approach. The study first explicates the maxim and the three focal issues, followed by an assessment of how the maxim may be applied to each case. The findings demonstrate that the maxim is applicable across the three contexts under consideration, underscoring the primacy of preventing harm even at the expense of relinquishing certain benefits. The analysis reveals that both early marriage and polygamy without spousal consent generate harms that outweigh their purported benefits, and should therefore be eschewed in light of the maxim. With respect to marital dissolution on the grounds of infertility, the applicability of the maxim is contingent upon the specific circumstances of the spouses. Where the marriage remains harmonious notwithstanding the absence of offspring, the prevention of dissolution is prioritized. Conversely, where infertility constitutes a persistent source of marital discord, dissolution may serve as a viable recourse to avert greater harm.